2017
DOI: 10.1111/jth.13664
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of cancer‐related isolated distal deep vein thrombosis: the OPTIMEV study

Abstract: Background Isolated distal deep vein thrombosis (iDDVT) (infra-popliteal DVT without pulmonary embolism [PE]) is a frequent event and, in the absence of cancer, is usually considered to be a minor form of venous thromboembolism (VTE). However, the clinical significance of cancer-related iDDVT is unknown. Methods Using data from the observational, prospective multicenter OPTIMEV cohort, we compared, at 3 years, the incidences of death, VTE recurrence and major bleeding in patients with cancer-related iDDVT with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 25 publications
9
52
0
4
Order By: Relevance
“…Second, in our study, we found a 1‐year VTE recurrence at 6% with an overall incidence rate of 6.5 recurrent VTEs per 100 patient‐years in patients with IDDVT and active cancer despite receiving anticoagulant treatment. This was comparable to the findings in two recent studies by Dentali et al and Galanaud et al in which they found a high risk of recurrent VTEs in patients with IDDVT and cancer . These studies together support initial treatment with anticoagulation in this population as the rate of VTE recurrence would presumably be much higher with a serial monitoring approach.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Second, in our study, we found a 1‐year VTE recurrence at 6% with an overall incidence rate of 6.5 recurrent VTEs per 100 patient‐years in patients with IDDVT and active cancer despite receiving anticoagulant treatment. This was comparable to the findings in two recent studies by Dentali et al and Galanaud et al in which they found a high risk of recurrent VTEs in patients with IDDVT and cancer . These studies together support initial treatment with anticoagulation in this population as the rate of VTE recurrence would presumably be much higher with a serial monitoring approach.…”
Section: Discussionsupporting
confidence: 90%
“…First, although the results of the CACTUS trial demonstrated a self‐limited course of IDDVTs in low‐risk patients, the optimal treatment of higher risk patients remained unknown . We confirmed findings in other studies that IDDVTs associated with cancer have an increased risk of VTE recurrence . Second, in our study, we found a 1‐year VTE recurrence at 6% with an overall incidence rate of 6.5 recurrent VTEs per 100 patient‐years in patients with IDDVT and active cancer despite receiving anticoagulant treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This observation indicates that cancer is the main risk factor to be considered for the development of adverse events after IDDVT. Consistently, the results of the two OPTIMEV sub-studies focusing on the 3-year rate of recurrence and death after cancer-associated DVT [24] and on subsequent cancer diagnosis after unprovoked DVT [13] suggested no differences between IDDVT and PDVT patients. It remains to be confirmed whether a more aggressive or diffused cancer is associated with a more proximal site of presenting DVT.…”
Section: Resultsmentioning
confidence: 56%
“…For CAT, we include any proximal or symptomatic distal lower extremity deep vein thrombosis (DVT) and/or incidental or symptomatic pulmonary embolism. Symptomatic distal DVTs were included, as these are routinely treated in cancer patients, and a recent study has confirmed that in cancer patients, distal DVTs have a comparable risk of VTE recurrence as proximal DVTs …”
Section: Methodsmentioning
confidence: 99%